Foundations of Kurikulum Merdeka development in elementary education (from a philosophical perspective) - Abdul Rahman; Babang Robandi (Inovasi Kurikulum, 2024)
The mismatch of philosophical foundations often causes the ineffectiveness of curriculum implementation. Ideally, the philosophical basis of a curriculum guides its implementation direction. This research examines the philosophical foundation for developing primary education curricula, particularly the Kurikulum Merdeka. The method employed Library Research by sourcing data from nationally and internationally indexed journals. This study is crucial to understanding the philosophical basis underlying the "Kurikulum Merdeka" in primary education. Findings reveal diverse approaches in the learning process, reinforcement of specific values, and a unique focus in preparing students for complex societal life. The Kurikulum Merdeka in basic education is based on various philosophical schools ranging from idealism, realism, pragmatism, existentialism, and perennialism to progressivism, reconstructivism, postmodernism, and humanism in education to create a learning environment that is diverse, responsive, and relevant for students' overall development. By applying these streams, the curriculum aims to create a responsive and holistic learning platform that caters to students' needs in this ever-evolving era. Abstrak Ketidakefektifan implementasi kurikulum sering kali disebabkan oleh ketidaksesuaian landasan filosofi yang digunakan. Landasan filosofi sebuah kurikulum memperjelas arah implementasinya. Penelitian ini bertujuan mengamati landasan filosofis yang digunakan dalam pengembangan kurikulum pendidikan dasar, khususnya Kurikulum Merdeka. Metode pada penelitian ini menggunakan studi kepustakaan dengan pengambilan data dari jurnal yang terindeks nasional dan internasional yang memiliki kaitan dengan Kurikulum Merdeka. Penelitian ini penting untuk memahami dasar filosofis yang melandasi Kurikulum Merdeka pada pendidikan dasar. Hasilnya menunjukkan beragam pendekatan dalam proses pembelajaran, penguatan nilai-nilai khusus, dan fokus unik dalam mempersiapkan siswa menghadapi masyarakat yang kompleks. Kurikulum Merdeka pada pendidikan dasar didasarkan pada berbagai aliran filsafat mulai dari idealisme, realisme, pragmatisme, eksistensialisme, perenialisme, hingga progresivisme, rekonstruktivisme, postmodernisme, dan humanisme dalam pendidikan untuk menciptakan lingkungan pembelajaran yang beragam, responsif, dan relevan bagi perkembangan siswa secara menyeluruh. Dengan menerapkan aliran-aliran ini, kurikulum tersebut bertujuan menciptakan platform pembelajaran yang responsif dan holistik bagi kebutuhan siswa di era yang terus berkembang. Kata Kunci: Landasan filosofis; pengembangan kurikulum; pendididkan dasar